The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1142/s0219720004000946
|View full text |Cite
|
Sign up to set email alerts
|

Robustness, Stability and Efficiency of Phage Λ Genetic Switch: Dynamical Structure Analysis

Abstract: Based on the dynamical structure theory for complex networks recently developed by one of us and on the physical-chemical models for gene regulation, developed by Shea and Ackers in the 1980's, we formulate a direct and concise mathematical framework for the genetic switch controlling phage lambda life cycles, which naturally includes the stochastic effect. The dynamical structure theory states that the dynamics of a complex network is determined by its four elementary components: The dissipation (analogous to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
95
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(99 citation statements)
references
References 42 publications
(126 reference statements)
2
95
0
2
Order By: Relevance
“…Our findings support the model that stability against prophage induction largely results from cooperative DNA binding by CI 2 to the O R 1 and O R 2 sites (22, 23). Zhu et al also showed the importance of cooperativity between CI dimers in an earlier computational study (10). The finding emerging from this study is that the cooperativity of Fig.…”
Section: Probability Landscape Of Phage Lambda In Lysogenic and Lyticsupporting
confidence: 73%
See 2 more Smart Citations
“…Our findings support the model that stability against prophage induction largely results from cooperative DNA binding by CI 2 to the O R 1 and O R 2 sites (22, 23). Zhu et al also showed the importance of cooperativity between CI dimers in an earlier computational study (10). The finding emerging from this study is that the cooperativity of Fig.…”
Section: Probability Landscape Of Phage Lambda In Lysogenic and Lyticsupporting
confidence: 73%
“…Because reactions often involve only low copy numbers of molecules and have large separations in timescale, stochasticity has a strong influence on the behavior of molecular networks (3,4,10). Deterministic models based on the principles of mass action are often incapable of capturing the multistable nature of the network when copy numbers are small (11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in their analysis of the robustness of phage 's lysogenic phase (55), Aurell et al (56) and Zhu et al (57) assumed that monomers and dimers were degraded with equal rates and concluded that additional source(s) of cooperativity are needed to explain the observed robustness. We suggest that cooperative stability might be another possible source of cooperativity that needs to be examined critically.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental and theoretical studies are steadily advancing our knowledge of the wiring and input-output characteristics of a variety of natural and designed biological networks. These efforts have focused on characterizing the components and interactions for specific biological networks and their dynamical behaviors, by using standard genetic and biochemical approaches in conjunction with mathematical analysis of discovered circuits (1)(2)(3)(4)(5)(6)(7). Valuable insights into certain design features of biological networks have emerged through these efforts (8)(9)(10)(11)(12)(13) and are used to guide the design of synthetic systems (14)(15)(16).…”
mentioning
confidence: 99%